Represi Kepada LGBT Dalam Pemberitaan Media Online Larangan Dukungan One Love Di Piala Dunia Qatar - Lobodally, Altobeli (AGUNA: Jurnal Ilmu Komunikasi, 2024)
The Qatar 2022 Football World Cup with the issue of banning voicing support for LGBT has been in the spotlight for several mass media. Including the Indonesian mass media that packs German shut-up news that supports LGBT, with shades of Islamic breathing sentences. The choice of words and sentences is nothing more than an attempt to repress LGBT as folk devils and become a moral panic that is worth the profit. This research aims to uncover LGBT repression in the news of the ban on One Love's support at the 2022 Qatar World Cup. The research will use the theory of Moral panic and treat the news as a text that will decipher each word and sentence. Thus, the social semiotics of M.A.K. Halliday will be used as a research method. This study found that LGBT is only a means of fighting between the European camp and the Arab camp. LGBT advocates are labeled as frontal and defiant opposers. This news uses the figure of speech Pars Pro Toto, which seems to be on behalf of all parties even though it is not. This news adds to the hatred and repression of LGBT people who feel only profit.